MULTIPURPOSE (WEARPROOF AND ANTIFRICTIONAL) COVERINGS ON PRODUCTS FROM CAST IRON - A. P. Laskovnev; A. I. Garost; A. I. Pokrovsky (Литьë и металлургия)
The basic elements of the new complex technologies providing effective receiving of the materials with the new level of properties are considered. Prospects of creation of new systems for alloying of constructional materials for mechanical engineering with management of their primary crystal structure, hardening mechanisms and resistance to fragile destruction are noted. The resource-saving method of direct surface alloying and modifying (using oxides) is developed. Industrial wastes and semi-products of adjacent processes are used as modifying additives. The metals reduction is made by atomic hydrogen and carbon from the special coverings of a casting mold and cores containing high-polymeric connections.